Ovarian Sparing Surgery in Mature Ovarian Teratomas in Children: A 20-Year Single-Center Experience - Szymon, Olga; Bogusz, Bartosz; Taczanowska-Niemczuk, Anna; Maślanka, Marcin; Górecki, Wojciech (European Journal of Pediatric Surgery, 2020)
Introduction Despite its benign nature, possible bilateral presentation, and a very good prognosis, ovarian sparing tumorectomy (OST) in mature ovarian teratoma (MOT) is not commonly performed. Unilateral oophorectomy has physiological consequences, while bilateral is devastating. The aim of this study is promotion of OST in MOT among children.Materials and Methods We reviewed 120 patients operated for MOT between August 1999 and 2019.Results Ovariectomy was performed in 15 patients (14 between 1999 and 2009 and 1 after 2010). In 105 girls, OST was possible including 32 with ovarian torsion. The approach was laparoscopy in 30 girls (11 conversions) and laparotomy in 94. Intra-abdominal spillage occurred in 30% of laparoscopic dissections. Postoperative morbidity was not associated with surgical approach (p = 0.613) or presence of adnexal torsion (p = 0,608). Follow-up was from 4 months to 9 years (median = 4 years) with access to 90% of patients. Bilateral lesions were observed in six (synchronous in five and metachronous in one) patients. Recurrence appeared in three patients operated via laparotomy and OST (after 12, 46, and 74 months). In one girl, asynchronous contralateral MOT was found 5 years after unilateral oophorectomy. Ovarian regeneration after torsion was observed in sonography in 84.4% of the patients. None of the patients experienced chemical peritonitis or malignant tumor transformation.Conclusion OST is safe and effective and should be the first-line procedure in children. Laparoscopy and laparotomy constitute a complementary approach to MOT. Ultrasound follow-up is necessary to monitor recurrence, contralateral disease, and ovarian regeneration.
Keywords: ovarian teratoma; ovarian preservation; pediatric; follow-up